2022
DOI: 10.1186/s12887-022-03520-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prevalence and severity of asthma, rhinitis, and eczema among schoolchildren (6–7 and 13–14 years old) in Khuzestan, Iran: a cross-sectional survey

Abstract: Background Asthma and allergic complications are the most common chronic disorders in children and adolescents. This study aimed to determine the prevalence and severity of asthma, allergic rhinitis, eczema among schoolchildren, and some related risk factors. Methods The cross-sectional study was performed in 2019 and involved 4000 students aged 6–7 years and 4000 students aged 13–14 years (both girls and boys) from urban schools in Khuzestan Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…It is reported that bronchial asthma remains the most common noncommunicable lung disease, the prevalence of which is the highest in middle-and low-income countries [75][76][77][78][79]. The danger of this disease is increased during an asthma attack, which, due to the narrowing of the bronchial lumen, significantly impairs lung ventilation and therefore causes the development of hypoxia [80,82].…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that bronchial asthma remains the most common noncommunicable lung disease, the prevalence of which is the highest in middle-and low-income countries [75][76][77][78][79]. The danger of this disease is increased during an asthma attack, which, due to the narrowing of the bronchial lumen, significantly impairs lung ventilation and therefore causes the development of hypoxia [80,82].…”
Section: Resultsmentioning
confidence: 99%
“…In the later study, it was demonstrated that, after adjusting for the effects of other lifestyle factors, adolescents were significantly more likely to have suffered from atopic dermatitis if they were female or asthmatic, indicating a direct effect of nearly the same magnitude as observed in the present study 20 . Another study from the region found that adolescents with atopic dermatitis were significantly more likely to be asthmatic 21 . A study from Lebanon showed that a mother’s waterpipe smoking was significantly associated with atopic dermatitis with a TE, which was somewhat higher than the TE reported in the present study 3 .…”
Section: Discussionmentioning
confidence: 98%
“…The eggs in the feces can become infective, and they can reach various water sources such as rivers, streams, sewage systems, and consequently, they enter agricultural fields, and contaminate vegetables [22,46]. It is notable that population in Khuzestan are faced with inadequate allocation of health care facilities and environmental challenges such as dust storms, floods, water crises, and infrastructural deficiencies [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%